Pellavalujitteiset komposiitit - Vilppunen, Pekka (Maatalouden tutkimuskeskus, 2000)
Komposiittimateriaalien tuotanto on voimakkaasti kasvava luonnonkuitujen sovellusalue. Pellavalla voidaan mm. korvata lasikuituja kovaa kulutuskestävyyttä vaativien osien valmistuksessa esimerkiksi autoteollisuudessa. Pellavan entsymaattista käsittelyä on jo käytetty hajottamaan kuituja korressa kiinnipitävää pektiiniä. Jatkuvalla entsymaattisella liotuksella voidaan tuottaa laadullisesti ja taloudellisesti kilpailukykyistä lujitekuitua muovisovellutuksiin. Tutkimuksessa pellavakuitua käytettiin lujitekuituna kertamuovivalmisteissa. Tuotteiden lujuudet olivat luokkaa 800 1000 Mpa ja jäykkyydet 80 Gpa.

Flax is an important source of natural fibres for technical use e.g. in composite materials. Degumming of the flax with microbes and enzymes has been studied at length. Producing and characterizing microbial plant degradative enzymes under strictly controlled conditions have important practical and economic implications. Enzymatic retting is a continuous process that produces high-quality flax fibres during the controlled maceration of flax with the aid of different enzyme preparations. The controlled retting process developed by the project (1997 1999) produces fibre of uniform quality for reinforced plastics. Scanning electron microscopy and the tensile properties of flax/epoxi composites were used to evaluate the quality of enzymatically retted flax fibres. The results showed that the flax fibres have a modulus of about 80 Gpa and a strength of about 800 1000 Mpa.
Keywords: Ka; pellavat; kuidut; entsyymit; flax; fibres; enzymatic retting; composites